2010
DOI: 10.1080/13632752.2010.497660
|View full text |Cite
|
Sign up to set email alerts
|

First Step to Success – a school/home intervention program for preventing problem behaviors in young children: examining the effectiveness and social validity in Turkey

Abstract: This study examined the effectiveness of the First Step to Success (FSS) early intervention program for preventing antisocial behavior in Turkey. Participants included 24 students, their teachers and parents from four K-8 elementary schools. The experimental group included 12 targeted students (four kindergarten, four first-grade and four secondgrade students) who received the intervention. Both quantitative and qualitative methods were carried out by using a pre-posttest experimental design. Results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…In another study, Kucuker, CeberBakkaloglu and Sucuoglu (2001) indicated that early education programmes regulated the interaction behaviours between mothers and fathers and their children. On the other hand, Diken, Batu and Kurtyilmaz (2010) pointed out that early childhood education programmes had positive impacts on preventing problematic behaviours. With regards to special education services in early childhood, McConnell (2000) indicated that screening systems for children took place in each state of the USA.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In another study, Kucuker, CeberBakkaloglu and Sucuoglu (2001) indicated that early education programmes regulated the interaction behaviours between mothers and fathers and their children. On the other hand, Diken, Batu and Kurtyilmaz (2010) pointed out that early childhood education programmes had positive impacts on preventing problematic behaviours. With regards to special education services in early childhood, McConnell (2000) indicated that screening systems for children took place in each state of the USA.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In Turkey, First Step to Success has been applied in kindergarten and primary school classes, and positive effects from the program on antisocial behaviors and social skills have been found (Çelik, 2012;Diken, Cavkaytar, Batu, Bozkurt, & Kurtyılmaz, 2010. Other studies in international and national literature have evaluated the efficiency of First Step to Success Early Intervention Program from various aspects .…”
Section: Firstmentioning
confidence: 99%
“…In addition, there are studies that have found out the program's positive contributions to teachers (Blalock, 2008;Sprague & Perkins, 2009) and other students (Sprague & Perkins, 2009). Most of the studies that were reviewed were conducted through single subject (Beard & Sugai, 2004;Golly et al, 2000;Lien-Thorne & Kamps, 2005;Özdemir, 2011;Rodriguez, Sheldon, Loman, & Horner, 2009;Russell-Carter & Horner, 2007Sprague & Perkins, 2009) and experimental research designs Diken et al, 2010;Seeley et al, 2009;Sumi et al, 2012;Walker et al, 2009;Walker, Kavanagh, et al, 1998). However, a number of the studies using qualitative data collection techniques and describing the views of people who have a key role in the application of the program, including program counselors, teachers, and family, are limited (Diken & Rutherford, 2005;Overton, McKenzie, King, & Osborne, 2002).…”
Section: Firstmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that the program was effective in terms of decreasing problem behaviors both at home and at school, and it caused positive behaviors and teacher attitudes in class. Moreover, participants were happy with the program (see Beard & Sugai, 2004;Carter & Horner, 2009;Diken & Rutherford, 2005;Diken, Cavkaytar, Batu, Bozkurt, & Kurtyılmaz, 2010;Diken, Cavkaytar, Batu, Bozkurt, & Kurtyılmaz, 2011;Diken, Bozkurt, Arıkan et al, 2011;Golly, Sprague, Walker, Beard, & Gorham, 2000;Rodriguez, Loman, & Horner, 2009;Russell, 2006;Seeley et al, 2009). …”
mentioning
confidence: 99%